Arsitektur Digitalisasi Slot Sharing Agreement pada Pelayaran Rakyat (Pelra) - Rizki Eka Nafiandia; I Gusti Ngurah Sumanta Buana (Journal Software, Hardware and Information Technology, 2022)
This research focuses on the cargo hold rental system on the Pelra ship, which plays an important role in island connectivity which is categorized as PPKT (pulau-pulau kecil terluar). The purpose of this study is to identify the conventional cargo hold rental system and Pelra as well as the disengagement between agents. The method used is an empathy map and user persona which serves to identify the needs and objectives of the application prototype users. The purpose of this study is to identify the disengagement between Pelra parties by developing a cargo hold rental system in the form of a prototype, as well as forming a transformation strategy for implementing information system exchange. The method used is an empathy map and user persona which serves to identify the needs and objectives of the application prototype. The resulting prototype can simplify the cargo rental business process from 11 to 9 stages. Cost-benefit analysis is used to determine the feasibility of the prototype. The prototype is considered feasible because the feasibility ratio value is 1.133 so that it can be applied to the Pelra cargo hold rental process.